Lessons from genome skimming of arthropod‐preserving ethanol. (23rd June 2016) - Linard, B.; Arribas, P.; Andújar, C.; Crampton‐Platt, A.; Vogler, A. P.
Abstract: Field‐collected specimens of invertebrates are regularly killed and preserved in ethanol, prior to DNA extraction from the specimens, while the ethanol fraction is usually discarded. However, DNA may be released from the specimens into the ethanol, which can potentially be exploited to study species diversity in the sample without the need for DNA extraction from tissue. We used shallow shotgun sequencing of the total DNA to characterize the preservative ethanol from two pools of insects (from a freshwater habitat and terrestrial habitat) to evaluate the efficiency of DNA transfer from the specimens to the ethanol. In parallel, the specimens themselves were subjected to bulk DNA extraction and shotgun sequencing, followed by assembly of mitochondrial genomes for 39 of 40 species in the two pools. Shotgun sequencing from the ethanol fraction and read‐matching to the mitogenomes detected 40% of the arthropod species in the ethanol, confirming the transfer of DNA whose quantity was correlated to the biomass of specimens. The comparison of diversity profiles of microbiota in specimen and ethanol samples showed that 'closed association' (internal tissue) bacterial species tend to be more abundant in DNA extracted from the specimens, while 'open association' symbionts were enriched in the preservative fluid. The vomiting reflex of many insects also ensures that gut content is released into the ethanol, which provides easy access to DNA from prey items. Shotgun sequencing of DNA from preservative ethanol provides novel opportunities for characterizing the functional or ecological components of an ecosystem and their trophic interactions.